Potentiality of Pressmud Application in Soil for Palm Oil Plantation Productivity - Mohamad, Maheera; Razalli, Mohd Rizal; Kafi, Md Abdul; Noordin, Alminnourliza; Mustapen, Rosini Nawang; Ismail, Haikal; Chong, Khai Lin (2023)
The waste generated from the sugarcane industry was able to be the resource of another, bringing economic and environmental benefits. This study is able to generate positive outcomes for the sustainability of agriculture industry in Malaysia specifically for palm oil plantation. The agricultural sector of Malaysia comprises large oil palm and sugar refinery industry. Nearly 50% of the material resulted in organic waste with high lignin and cellulose content during palm oil and sugar production. This study can also enhance the green knowledge in soil technology for a sustainable agriculture industry in Malaysia. From the physico-chemical charateristics of this study, pressmud clearly shows a great material which having a higher potentiality to be an admixture medium in soil for palm oil plantation as to reduce the application of chemical fertilizer. Pressmud observed to have granular textured while laterite soil was less granular. The texture and surface became uneven and enclosed with pores. The addition of pressmud into the soil improves capability of the material to adsorb the nutrients through cation exchange process. Based on CEC, it can be concluded that the laterite soil-pressmud mixtures is suitable to be used soil amendment in enhancing the performance of the soil productivity for palm oil plantation.